Development of a Real-Time Thermoplastic Mask Compression Force Monitoring System Using Capacitive Force Sensor - Kim, Tae-Ho; Cho, Min-Seok; Shin, Dong-Seok; Shin, Dong Ho; Kim, Siyong (Frontiers in Robotics and AI, 2022)
For a thermoplastic mask to maintain clinical efficacy, the mask should wrap the patient surface properly and provide uniform pressure to all areas. However, to our best knowledge, no explicit method achieving such a goal currently exists. Therefore, in this study, we intended to develop a real-time thermoplastic mask compression force (TMCF) monitoring system to measure compression force quantitatively. A prototype system was fabricated, and the feasibility of the proposed method was evaluated.The real time TMCF monitoring system basically consists of 4 force sensor units, a microcontroller board, a control PC and an in-house software program. To evaluate the reproducibility of the TMCF monitoring system, both reproducibility test using a micrometer and setup reproducibility test using a head phantom were performed. Additionally, the reproducibility tests of mask setup and motion detection tests were carried out with a cohort of 6 volunteers. The system provided stable pressure readings in all of 10 trials during the sensor unit reproducibility test. The largest standard deviation (SD) among trials was about 36 gf/cm2 (~2.4 % of full scale range). For 5 repeated mask setups on the phantom, the compression force variation of the mask was less than 39 gf/cm2 (2.6 % of full scale range). We were successful in making masks together with the monitoring system connected and demonstrated feasible utilization of the system. Compression force variations were observed among the volunteers and according to the location of the sensor (among forehead, both cheekbones, and chin). The TMCF monitoring system provided the information in real time whether the mask was properly pressing the human subject as an immobilization tool. With the developed system, it is possible to monitor the effectiveness of the mask in real time by continuously measuring compression force between the mask and patient during the treatment. The graphical user interface (GUI) of the monitoring system developed provides a warning signal when compression force of the mask is insufficient. Although the number of volunteers participated in the study was small, obtained preliminary results suggest that the system could ostensibly improve the setup accuracy of a thermoplastic mask.